Nowa sentymentalność. Przejawy świadomości konwergencyjnej w wybranych monodramach Jewgienija Griszkowca - Syska, Katarzyna (Przegląd Rusycystyczny, 2013)
Katarzyna Syska Uniwersytet Jagielloński, Kraków, Poland katarzyna.syska@gmail.com НОВАЯ СЕНТИМЕНТАЛЬНОСТЬ. ПРОЯВЛЕНИЯ КОНВЕРГЕНТНОГО СОЗНАНИЯ В ИЗБРАННЫХ МОНОДРАМАХ ЕВГЕНИЯ ГРИШКОВЦА Резюме В начале девяностых годов ХХ века литературные критики и литературоведы загово-рили о усилении сентиментальных тенденций в современной литературе. Среди прочих авторов «неосентименталистом» был признан драматург, театральный режиссер и актер Евгений Гришковец. Неосентиментальность в его текстах не сводится к литературной стилизации, но опирается на своеобразную архитектонику отношений Я–другой, которая состоит в максимальном сближении точек зрения этих субъектов. В настоя-щей статье проводится анализ конвергентных субъектно-субъектных отношений на материале монодрам Гришковца Как я съел собаку и Одновременно. THE NEW SENTIMENTALITY: CONVERGENT CONSCIOUSNESS IN YEVGENY GRISHKOVETS’S SELECTED MONODRAMAS Summary Since the early 1990s literary critics and scholars have been pointing out the increasing tendency to sentimentality in modern Russian literature. Among other authors marked as “Neo-Sentimentalists” is Yevgeny Grishkovets, a playwright, stage director, and actor. The new sentimentality in his plays cannot be reduced only to literary imitation; it is based on a certain architectonics of relationship between Same and other: the viewpoints of these two subjects are almost identical. The article analyses the convergent subject–object relationship in Grishkovets’s monodramas How I Ate a Dog and Simultaneously.